Should copper cables be phased out in the last mile? - Ibraheem Kateeb (Institute of Advanced Engineering and Science, 2012)
It is commonly held by industry and government that copper cable should be phased out in favor of an all fiber network or wireless. Conversely, fiber optics has been in use for decades without displacing copper based networks. Additionally, copper is still being deployed for broadband services. This raises the following fundamental question: Is there a place for copper cabling in providing broadband solutions in the near and far term?this paper develop comprehensive distinctions between twisted pair copper and alternatives for current and future broadband solutions while rebutting arguments for transitioning to all fiber networks. It also compares fixed solutions against wireless alternatives, and present new technologies that drive continued value of copper conductors in the outside plant. Present personal experiences as well as those from industry professionals on the unique benefits that copper solution has which cannot be replicated by fiber will be shared for the benefit of educating the audiences.The results will show great potential for continued use of twisted pair copper in broadband networks. In the process, it will prove that current socio-political thinking promoting all-fiber broadband networks is flawed.Finally, it will be showed how copper will maintain a complementary role to fiber and wireless technologies as world-wide broadband networks continue to be built out.